(untitled) (Raparin Journal of Humanities (RJH), 2024)
This paper investigates how females’ otherness is formed amidst layers of oppression related to the abuse of religion, politics, and traditions and how characters resist or rebel in both Fountain and Wind Through My Hair within the story collection known as Echoes from the Other Land (2010) by Ava Homa. It will also investigate the way Kurdish women feel ’othered’ exploring their ethnic identity, female identity, societal and patriarchal norms, and mix of state politics and religion, in addition to the way they behave and dress up in society as portrayed in the works. The works showcase the lives of Kurdish women in the face of various intersecting challenges in the patriarchal, ethno-centric, theocratic society of Iran. The paper sheds light on various issues related to women’s autonomy, cultural expectations, and gender inequality. In both works, characters resist and debunk the tradition as othered and marginalized females. The issues can be tackled through both postcolonial and intersectional feminism as the two are in line with the issues of women of developing countries who are identified as minorities and whose identity is suppressed.